2019
DOI: 10.1111/cen.13918
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional associations of sex hormones with leucocyte telomere length, a marker of biological age, in a community‐based cohort of older men

Abstract: Context: Telomeres protect chromosomes from damage, and shorter leucocyte telomere length (LTL) is a marker of advancing biological age. The association between testosterone (T) and its bioactive metabolites, dihydrotestosterone (DHT) and oestradiol (E2) with telomere length, particularly in older men, is uncertain. The study aimed to clarify associations of sex hormones with LTL in older men. Participants and methods:We used cross-sectional data from 2913 men aged 76.7 ± 3.2 years with morning blood samples a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Estrogen-induced increased telomerase activity was demonstrated in several cell lines (54,55,56). Although telomerase activity is repressed in most somatic tissues, in highly proliferative tissues such as hematopoietic system, digestive system, and skin, TERT is still expressed (57), which makes possible the regulation of the TERT gene by estrogens (58).…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen-induced increased telomerase activity was demonstrated in several cell lines (54,55,56). Although telomerase activity is repressed in most somatic tissues, in highly proliferative tissues such as hematopoietic system, digestive system, and skin, TERT is still expressed (57), which makes possible the regulation of the TERT gene by estrogens (58).…”
Section: Discussionmentioning
confidence: 99%
“…Female testosterone levels are ten times lower than male's testosterone levels, conversely oestrogen levels in males are lower than females. Serum estradiol levels, the most potent form of oestrogen in reproductive aged women, have been positively correlated with leucocyte telomere length (Yeap et al., 2019). For post‐menopausal women, who experience a significant decline in estradiol levels, long‐term oestrogen therapy is associated with longer telomere lengths when compared to post‐menopausal women who have never taken hormone therapy (Lee et al., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…17 Additionally, it was observed that SHBG levels were independently and inversely correlated with LTL, suggesting that sex hormones may counteract the natural age-related decline in telomere length. 18,19 This association, particularly prominent among older individuals, highlights the potential role of sex hormones in preserving telomere integrity. 18 Multiple studies have shown that higher SHBG levels are related to a decline in BMD in both males and females, indicating a significant negative correlation between SHBG and osteoporosis.…”
Section: Introductionmentioning
confidence: 98%
“…A large population‐based cohort study has revealed a noticeable trend of increasing SHBG levels with advancing age 17 . Additionally, it was observed that SHBG levels were independently and inversely correlated with LTL, suggesting that sex hormones may counteract the natural age‐related decline in telomere length 18,19 . This association, particularly prominent among older individuals, highlights the potential role of sex hormones in preserving telomere integrity 18 .…”
Section: Introductionmentioning
confidence: 99%